Download presentation
Presentation is loading. Please wait.
1
Division of Polynomials
2
Divide a polynomial by a monomial
We can carry out the division term by term. dividend 2 ) 8 ( + x divisor 2 8 + = x Rough Work x 2 8 + 2 8 + = x x 1 4 Divide the polynomial term by term. 4 + = x The result (quotient) is x + 4 and the remainder is equal to 0. We say that 2x2 + 8x is divisible by 2x.
3
You may also use the method of long division.
Quotient x 2 x 2 8 x 4 + Divisor 2 x Dividend 2 x + 8 x 2 x 8 x 8 x Remainder = 0
4
Long division (divisor is not a monomial)
Consider the long division of ). 1 2 ( ) 3 6 8 + x Step 1 3 6 8 1 2 x + 4 x 2 8 Step 2 2 8 x + 1 3 6 4 8 2 x (+ 1)(+ 4x) Step 3 4 8 3 6 1 2 x + 4 x + 3 2 + x Subtract 8x2 + 4x from 8x2 + 6x + 3.
5
Step 4 4 8 3 6 1 2 x + + 1 x 2 Step 5 2 x 4 8 3 6 + 1 2 x (+ 1)(+ 1) Step 6 4 8 3 6 1 2 x + 1 + Subtract 2x + 1 from 2x + 3. 2
6
4 8 3 6 1 2 x + divisor ∵ Degree of 2 = 0, degree of 2x + 1 = 1 ∴ Degree of 2 < degree of 2x + 1 ∴ Stop the division process. remainder ∴ Quotient = 4x + 1, remainder = 2 Since the remainder is not equal to 0, we say that 8x2 + 6x + 3 is not divisible by 2x + 1.
7
Follow-up question Find the quotient and the remainder of (3x2 + 2x3 – 9) (2x – 1). 1. Rearrange the terms in descending powers of x. 2. Insert the missing term ‘0x’. 2 x 2 + x 1 + 9 3 2 1 - + x 2 3 - x x2(2x – 1) = 2x3 – x2 4 2 + x - 9 2 4 - x 2x(2x – 1) = 4x2 – 2x 9 2 - x ∴ Quotient = x2 + 2x + 1 Remainder = -8 1 2 - x 1(2x – 1) = 2x – 1 8 -
8
What is the relation among the dividend, divisor, quotient and remainder?
4 divisor 29 6 dividend 24 29 = remainder 5 In arithmetic, dividend = divisor quotient + remainder
9
This is known as the division algorithm.
In fact, the mentioned relation is also true for polynomials. Consider f(x) p(x). Let Q(x) and R(x) be the quotient and the remainder respectively. ) ( x Q R f p M dividend = divisor quotient + remainder f(x) = p(x) Q(x) R(x) degree of R(x) < degree of p(x) This is known as the division algorithm.
10
From the above result, we have 8x2 + 6x + 3 (2x + 1)(4x + 1) + 2
e.g. (8x2 + 6x + 3) (2x + 1) 4 8 3 6 1 2 x + From the above result, we have 8x2 + 6x + 3 (2x + 1)(4x + 1) + 2 dividend divisor quotient remainder
11
= (x + 3)(2x – 1) + 5 = (x + 3)(2x) – (x + 3)(1) + 5
When a polynomial is divided by x + 3 , the quotient and the remainder are 2x – 1 and 5 respectively. Find the polynomial. By division algorithm, we have the required polynomial = (x + 3)(2x – 1) + 5 = (x + 3)(2x) – (x + 3)(1) + 5 = 2x2 + 6x – x – 3 + 5 = 2x2 + 5x + 2
12
Follow-up question When 3x2 + 10x – 5 is divided by a polynomial, the quotient and the remainder are x + 4 and 3. Find the polynomial. Let p(x) be the required polynomial. By division algorithm, we have dividend divisor quotient remainder ∴ The required polynomial is 3x – 2.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.